Information Sciences research trends in Mexico (2002-2021): Historical and bibliometric analysis of doctoral theses of the National Autonomous University of Mexico - Morán-Reyes, Ariel Antonio (Iberoamerican Journal of Science Measurement and Communication, 2021)
Objective. The research and training trends in Information Sciences in Mexico were examined, based on the doctoral theses of the Postgraduate Program in Library and Information Science of the National Autonomous University of Mexico, during the period January 2002-March 2021. Design/Methodology/Approach. The documentary research method was used to provide a historical overview. This method was combined with bibliometric techniques to analyze output indicators such as the year of the thesis defense, supervisors, knowledge areas, and research lines. Results/Discussion. The results revealed a wide thematic diversity and the high applied character of the doctoral researches. Problem-solving in library education and documentary heritage studies were the most explored topics. Conclusions. The development of research and training trends in Information Sciences in Mexico through doctoral theses presents a concentration on certain topics; however, from a metatheoretical point of view, there is a dispersion of approaches. Originality/Value. This paper offers systematized and updated results, as well as relevant historical notes, on the development of doctoral research in Information Sciences in Mexico during the period 2002-2021.